High temperature tensile properties of the TI6242 alloy fabricated via selective laser melting - Tseng, Yean Tyng (Nanyang Technological University, 2022)
For many years, Titanium and its alloys have been utilized in many industries including aerospace. In the aerospace industry, they can be found in the airframe sections, disks and rotors and other engine parts due to their superior characteristics such as high strength, fracture toughness and resistance to fatigue. A favourable composition of Titanium alloy is often found in the industry, Ti-6-Al-4V (Ti64), which mainly service at lower operating temperatures up to 350°C. However, there are potential areas within the aircraft needing the benefits of Titanium alloy to service at higher operating temperatures. Thus, in this project, Ti-6Al-2Sn-4Zr-2Mo (Ti6242) will be investigated at higher temperatures. An additive manufacturing method, Selective Laser Melting (SLM) is used to manufacture Ti6242. The SLM could address the drawbacks of the poor machinability of Ti6242 as it can produce intricate and complex parts directly from the computer-aided design file without additional machining. The specimens will undergo heat treatment to stabilize the combination of ductility and strength after SLM. Microstructural examinations will be facilitated to elucidate the relationship among the mechanical properties and microstructure. The microstructural characteristics of Ti6242 alloy will be investigated via scanning electron microscope in the as built and the states after heat treatment. The fracture surface will be analysed to suggest the deformation behaviour and mechanism. The finding indicates that the SLM-fabricated Ti6242 alloy could exhibit comparable tensile properties relative to those of conventionally fabricated counterparts.